Evaluasi Standar Operasional Prosedur Kerja Housekeeping Departement dalam Penyediaan Kelengkapan Guest Supplies di Hotel Four Seasons Jakarta - Latif, Latif; Gilang Permana (TOBA: Journal of Tourism, Hospitality, and Destination, 2023)
Product and service quality in hospitality has an important role. Providing good service quality will lead to satisfaction for guests who stay overnight. Therefore, standard operating procedures for handling the completeness of guest equipment must be considered in preparing it. The purpose of this study was to find out the handling of guest equipment inventory in each room of the guests who stay so that guests feel satisfied and they will come again and will sell the hotel to family and friends. This research method uses a descriptive approach to finding service and hospitality to guests in creating guest satisfaction by providing lodging services and offering a variety of complementary facilities, such as restaurants, cafes, meeting rooms, and other services. The study results indicated that there were inventories that were not by standard operating procedures. The occurrence of a shortage of guest equipment in guest rooms could have an impact on decreasing the services provided by the hotel. Solutions made by housekeeping in dealing with the shortage of guest equipment in rooms had to be addressed immediately to ensure guest satisfaction was maintained. In addition, it is important to note that the goal of the hospitality industry is to create a pleasant experience for guests who stay. In this case, service and hospitality to guests is crucial. Through good service quality, guests will feel valued and cared for, so they will tend to return to stay at the hotel and even promote it to their family and friends and it is hoped that these things can help improve service quality and guest satisfaction.